Folding and Evolution of a Repeat Protein on the Ribosome - León-González, José Alberto; Flatet, Perline; Juárez-Ramírez, María Soledad; Farías-Rico, José Arcadio (Frontiers in Molecular Biosciences, 2022)
Life on earth is the result of the work of proteins, the cellular nanomachines that fold into elaborated 3D structures to perform their functions. Just recently, we started to recognize that proteins can fold during translation on the ribosome (process known as cotranslational folding). In this perspective article we discuss current advances in our understanding of the field and provide original data that highlight the role of ribosome in the evolution of protein structures. First, we used the sequence of the Ankyrin domain from the Drosophila Notch receptor to launch a deep sequence-based search. With this strategy we found a conserved 33-residue motif shared by different protein folds. Then to see how the vectorial addition of the motif would generate a full structure we measured the folding on the ribosome of the Ankyrin repeat protein. Not only the on-ribosome folding data is in full agreement with classical in vitro biophysical measurements but also it provides experimental evidence on how folded proteins could have evolved by duplication and fusion of smaller fragments. Overall, we discuss how the ribosomal exit tunnel could be conceptualized as an active site that is under evolutionary pressure to influence protein folding.